2008
DOI: 10.1590/s0073-47212008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Associações de peixes na região costeira de Itaipu, Niterói, RJ

Abstract: ABSTRACT. Associations of fishes in the coastal region of Itaipu, Niterói. The coastal region of Itaipu, Rio de Janeiro forms a partially sheltered sound, protected by three islands, but still maintaining full communication with the open sea. The sound also receives fresh water input from the Itaipu-Piratininga lagoon system, constituting an area of intense artisanal fisheries. Using data from monthly monitoring of the artisanal fisheries (beach seining, gill netting and hand lining), experimental surf zone be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
2
13
0
6
Order By: Relevance
“…Furthermore, the small size of the individuals increases their agility in shallow coastal water connectivity between the fish assemblage. This connectivity between beaches and estuarine environments has been described for subtropical environments (Monteiro-Neto et al, 2008) for species of Clupeiformes, and also in a study by Xavier et al (2012) that observed connectivity between reef systems and mangroves within the same study area.…”
Section: Influence Of Environmental Factorssupporting
confidence: 77%
“…Furthermore, the small size of the individuals increases their agility in shallow coastal water connectivity between the fish assemblage. This connectivity between beaches and estuarine environments has been described for subtropical environments (Monteiro-Neto et al, 2008) for species of Clupeiformes, and also in a study by Xavier et al (2012) that observed connectivity between reef systems and mangroves within the same study area.…”
Section: Influence Of Environmental Factorssupporting
confidence: 77%
“…Coastal zones are areas of ecological transition sites that enable a connection between terrestrial and marine ecosystems, through genetic and biomass exchanges, characterizing them as dynamic and biologically diverse environments (Robertson & Lenanton 1984, Monteiro-Neto et al 2008. Sandy beaches can occur in any type of coast subject to the availability and sufficient volume of sediments to be deposited by the waves above the sea level (Veloso & Neves 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Micropogonias furnieri) are distributed across sandy bottom fishing spots, or that such spots are more readily accessible to fishers most of the time. For instance, the artisanal fishery at Itaipu (CPZ8) concentrates its gill net fishing effort over similar sandy bottom habitats, capturing mostly M. furnieri (Tubino et al, 2007;Monteiro-Neto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A similar matrix of species vs fishing gear type was subjected to the same analysis to identify species groups co-occurring in one or more fishing gears. Both dendrograms were generated in the free software Paleontological Statistics (PAST) version 2.17 (Hammer et al, 2001).Nodal analysis using the concepts of ecological constancy (the frequency of occurrence of a group of species in a given fishing spot group) and fidelity (how much a group of species is restricted to a certain fishing spot group, when comparing the individual group constancy to the average constancy of all groups) (Boesch, 1977;Monteiro-Neto et al, 2008), was used to express the relationship between species and fishing spot groups. The following arbitrary scale was established, based on Boesch (1977), considering the range of constancy and fidelity values observed: Constancy -high > 0.7; moderate between 0.5-0.7; low < 0.5; Fidelity -high > 2.0; moderate between 1.0-2.0; low < 1.0.…”
mentioning
confidence: 99%